Spirituality in brazilian nursing: a historical retrospect - de Sá, Ana Cristina; Pereira, Luciane Lúcio (O Mundo da Saúde, 2007)
Spirituality is a subject present in nursing literature since Florence Nightingale. In Brazil, the first scientific publication appeared in 1947 and is now represented by the Revista Brasileira de Enfermagem [Brazilian Journal of Nursing]. This periodic reflects the trends of thinking about nursing in the country, for it publishes the better evaluated works presented in the Congresso Brasileiro de Enfermagem [Brazilian Congress of Nursing], a yearly event of Associação Brasileira de Enfermagem [Brazilian Association of Nursing] that happens since then. We did a historical survey of Brazilian nursing thought about spirituality from an active search of articles published by the said Journal from the decade of 1950 to the year 1999. 57 articles about the subject were found, and classified in 9 categories, namely: spirituality as part of the character and morality of the individual that chooses to study nursing; spirituality as a philosophy of work of nurses; spirituality as part of the curriculum and education of nurses; spirituality in patient assistance as a basic human necessity; the meaning of spirituality for those who are taken care of (patient/client); the meaning of spirituality for those who take care of; spirituality and humanization; spirituality, death and dying; and spirituality according to Ethics and Bioethics. One concluded that the thought of nurses in through these decades passed to variations in number and categories that reflect the evolution of science and the questions this generates.